Application of model order reduction to a finite element model of cryogenic turning. Issue 1 (18th November 2019) - Becker, Steven; Hotz, Hendrik; Kirsch, Benjamin; Aurich, Jan C.; Müller, Ralf
Abstract: Metastable austenitic steels offer the opportunity of a surface layer hardening integrated in the machining process. The hardening effect is achieved by a deformation induced austenite‐martensite phase transformation, for which high mechanical loads and low temperatures are necessary, typically below room temperature. These conditions can be accomplished during cryogenic turning, allowing a phase transformation in the surface layer of the workpiece. To study the austenite‐martensite transformation behavior, information about the temperatures in the contact zone between tool and workpiece during machining is necessary, which can hardly be measured. Therefore, FE simulations of the process are utilized to calculate the transient process temperatures. In this paper the idea of projection‐based model order reduction and its implementation into the finite element program FEAP are described, allowing a solution speed‐up while maintaining accuracy of the full‐order model.